Ontogeny informs regeneration: explant models to investigate the role of the extracellular matrix in cartilage tissue assembly and development. (3rd July 2020) - McCreery, Kaitlin P.; Calve, Sarah; Neu, Corey P.
ABSTRACT: Osteoarthritis (OA) is typically managed in late stages by replacement of the articular cartilage surface with a prosthesis as an effective, though undesirable outcome. As an alternative, hydrogel implants or growth factor treatments are currently of great interest in the tissue engineering community, and scaffold materials are often designed to emulate the mechanical and chemical composition of mature extracellular matrix (ECM) tissue. However, scaffolds frequently fail to capture the structure and organization of cartilage. Additionally, many current scaffold designs do not mimic processes by which structurally sound cartilage is formed during musculoskeletal development. The objective of this review is to highlight methods that investigate cartilage ontogenesis with native and model systems in the context of regenerative medicine. Specific emphasis is placed on the use of cartilage explant cultures that provide a physiologically relevant microenvironment to study tissue assembly and development. Ex vivo cartilage has proven to be a cost-effective and accessible model system that allows researchers to control the culture conditions and stimuli and perform proteomics and imaging studies that are not easily possible using in vivo experiments, while preserving native cell–matrix interactions. We anticipate our review will promote a developmental biology approach using explanted tissues to guide cartilage tissue engineering and inform new treatment methods for OA and joint damage.